The Influence of Intrinsic and Extrinsic Factors on the Purchase Intention of Green Skin Care Products Mediated by Consumer Belief - Olivia SUREJA; Dwinita LAKSMIDEWI (International Journal of Environmental, Sustainability, and Social Science, 2024)
The aim of this research is to analyse the direct influence of intrinsic and extrinsic cues on purchase intention among consumers who use both conventional and green skin care products. Additionally, the research will examine the indirect influence of these cues on purchase intention through consumer beliefs as a mediating variable. This study involved distributing questionnaires to 125 respondents from Generation Y and Generation Z who have lived on the island of Java for the past year and have used skin care and green skin care products. The sampling method used was non-probability sampling with a purposive sampling technique. Data analysis was conducted using the Structural Equation Model (SEM) analysis tool with SmartPLS 4. The results of this research indicate that intrinsic and extrinsic cues significantly influence consumer beliefs. Furthermore, intrinsic cues, extrinsic cues, and consumer beliefs all have a significant effect on purchase intention. The study also confirms that consumer beliefs effectively mediate the influence of intrinsic and extrinsic cues on purchase intention. Keywords : Intrinsic Cues, Extrinsic Cues, Customer Belief, Green Product